Using a wiki to collect student work in Vector Calculus. Issue 7 (9th August 2021) - Glynn-Adey, Parker
Abstract : In this classroom note, we describe the use of a wiki to aggregate student solutions to calculation-based mathematics problems. We outline the setup of the wiki used to support this project, the administrative issues involved in running a wiki, and student reaction to the wiki project. We will describe how students participated, and were assessed, as they co-created the wiki. We conclude with practical advice for people looking to use wikis in their classes.